Reaching the Poor with Health, Nutrition, and Population Services : What Works, What Doesn't, and Why. - Gwatkin, Davidson R.; Wagstaff, Adam; Yazbeck, Abdo (World Bank e-Library., 2005)
This volume presents eleven case studies that document how well or poorly health, nutrition, and population programs have reached disadvantaged groups in the countries of Africa, Asia, and Latin America where they were undertaken. The studies were commissioned by the Reaching the Poor Program, undertaken by the Word Bank in cooperation with the Bill and Melinda Gates Foundation and the Dutch and Swedish governments, in an effort to find better ways of ensuring that health, nutrition, and population programs benefit the neediest. These case studies, reinforced by other material gathered by the.